Combined Effects of Exercise Training and Nutritional Supplementation in Cancer Patients in the Context of the COVID-19: A Perspective Study - Molanouri Shamsi, Mahdieh; Vahed, Alieh; Hekmatikar, AmirHossin Ahmadi; Suzuki, Katsuhiko (Frontiers in Nutrition, 2022)
The 2019 coronavirus (COVID-19) epidemic, has caused unprecedented global social and economic impacts and many deaths. Many risk factors have been identified in the progression of COVID-19 to severe stages, and it is shown that the coronavirus appears more severely in cancer. Pro-inflammatory status and weakened immune system due to cancer-related treatments can be determinants in the immune system's response to the coronavirus in these patients. Higher physical activity levels are associated with lower hospitalization rates and mortality in COVID-19. Also, regular exercise training can improve immune system responses, modulate inflammatory responses, and improve psychological parameters in cancer patients. The interactive effects of nutritional supplements on immune responses and anti-inflammatory status have been shown in some studies. The purpose of this perspective article was to investigate the interaction between dietary supplementation and regular physical exercise in controlling risk factors associated with coronavirus in cancer patients. In addition to appropriate dietary habits, some nutritional supplements, especially vitamin D, have been shown to improve the immune system's response against COVID-19 and cancer. Using lifestyle strategies such as regular physical activity and intake of functional compounds as supplements can be effective in treatment outcomes, quality of life, and overall survival in cancer patients. We proposed that combining dietary supplements and exercise training in cancer patients can boost immune responses against COVID-19 and probably improve vaccine responses. Angiotensin (ANG)-(1-7) Mas receptor axis can probably activate following exercise training and vitamin D combination. And can prevent pulmonary injury, hematological alterations, and hyperinflammatory state in COVID-19.